Synergetika a samoorganizace v ekonomice - Balúch, Pavel (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2012)
Diplomová práce je zaměřena na analýzu a výzkum synergie a samoorganizace v ekonomice. Motivací pro zpracování této diplomové práce bylo přistoupení České republiky a dalších devíti států do Evropské unie 1. května 2004. Primárním cílem bylo provézt analýzu problému a na modelovém příkladu za předpokladu „ceteris paribus“ potvrdit nebo vyvrátit myšlenku, zda má vstup do Evropské unie pozitivní synergický efekt pro nově přistupující státy. Dílčím problémem řešeným v diplomové práci je druhý význam synergie. Zde bylo analyzováno využití synergie v logistice a navrženy možnosti, ke zlepšení současného stavu.

The master thesis focuses at analysis and research of synergy and self-organization in economics. The motivation for the thesis was joining Czech Republic and other nine countries to the European Union on May 1st, 2004. The primary aim was to analyse the problem and on a model example,assuming "ceteris paribus", confirm or refute the thought, that joining the European Union has positive synergic effect for newcomers. The second meaning of synergy is solved as a sub-problem in the master thesis, where the use of synergy in logistics was analysed and opportunities improving the current situation were suggested.
Synergetics and Self-organization in the Economy
Keywords: Cyklus; Export; HDP; Nezaměstnanost; Přímé zahraniční investice; Rating; Úroky; Samoorganizace; Synergetika.; Cycle; Export; GDP; Unemployment; Foreign direct investment; Rating; Interest; Self-organization; Synergetics.